Scenes of explicit catholicism: the Pope and the political meanings of religion in Argentina - Bonnin, Juan Eduardo (2013)
This article analyzes the relationships between religious and political discourse in Argentina with regard to the recent election of Jorge Mario Bergoglio as the new Catholic Pope, Francis. In first place, we establish a theoretical distinction between "Catholicism" and "Church" in order to understand the historical complex bonds between religious and political discourse in Argentina. This will allow us to characterize Bergoglio as a skilful actor, who is able to move between different millieux, notably Catholicism and Church, to develop complex strategies in both of them. We observe these skills in four key issues in current social life in Argentina: the debates on equal marriage, the memories on the last dictatorship, the social agenda and the political system.